Optical coherence tomography in ischemic optic neuropathy - Fard, Masoud Aghsaei; Ghahvehchian, Hossein; Subramanian, Prem S. (Annals of Eye Science, 2020)
Ischemic optic neuropathies are among the most common causes of sudden vision loss, especially in patients over age 50. The cause and prognosis of these disorders, and in particular non-arteritic anterior ischemic optic neuropathy, is poorly understood, and treatments remain poor in terms of restoring or preserving vision. Optical coherence tomography (OCT) and OCT angiography have allowed us to identify early and late structural changes in the optic nerve head and retina that may assist in predicting visual outcomes and may lead to greater understanding of pathogenesis and thus the development of effective medical interventions.